PENDAMPINGAN DAN PELATIHAN PENGELOLAAN KEUANGAN SEDERHANA DI MA ROHMATUL UMMAH KARANGANOM KECAMATAN KARANGBINANGUN KABUPATEN LAMONGAN - Moh Ali Wafa; M. Hafidh Nashrullah; Moh. Azus Shony Azar; Ahmad Fathur Rozi (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
The implementation of this service is carried out at the Rohmatul Ummah Karanganom Karangbinangun Lamongan Islamic High School on March 1-30 2023, which aims to assist Madrasah in structuring madrasah financial management by making simple financial reporting (Excel) in financial reporting and carrying out assistance in carrying out recording of financial receipts and expenditures by using simple computerized reporting, it is hoped that the preparation of financial reports can be accurate and timely and accountable, in order to support the arrangement of adequate and transparent madrasah financial management. The method used is to form Focus Group Discussions (FGD), outreach and training related to effective financial management and the application of technology-based financial management. The results obtained in this service are the procurement of computerized technology-based programs (excel programs). The results of this service are able to improve the ability of Madrasah/partners to manage finances effectively. Madrasah / Partners can apply the concept of financial reporting and can prepare financial reports that are accountable and timely according to their needs. Keywords: Financial Management, Record keeping and bookkeeping ABSTRAK Pelaksanaan Pengabdian ini dilakukan di MA Rohmatul Ummah Karanganom Karangbinangun Lamongan pada 1-30 Maret 2023, yang bertujuan untuk membantu Madrasah dalam penataan pengelolaan keuangan madrasah dengan cara membuatkan pelaporan keuangan sederhana (Excel) dalam pelaporan keuangan dan melaksanakan pemdampingan dalam melaksanakan pencatatan penerimaan dan pengeluaran keuangan dengan menggunakan pelaporan sederhana dengan komputerisasi, yang diharapkan penyusunan laporan keuangan bisa akurat dan tepat waktu serta akuntabel , guna mendukung penataan pengelolaan keuangan madrasah yang memadai dan transparan Metode yang digunakan adalah membentuk Focus Group Discussion (FGD), sosialisasi dan pelatihan terkait dengan pengelolaan keuangan yang bagus dan pengaplikasian pengelolaan keuangan berbasis teknologi. Hasil yang didapatkan pada pengabdian ini adalah pengadaan program berbasis teknologi komputerisasi (program excel). Hasil dari pengabdian ini mampu meningkatkan kemampuan Madrasah/mitra dalam mengelola keuangan yang efektif. Madrasah /Mitra dapat menerapkan konsep pelaporan keuangan serta dapat Menyusun laporan keuangan yang akuntabel dan tepat waktu sesuai dengan kebutuhannya. Kata Kunci: Pengelolaan Keuangan, Pencatatan dan pembukuan